Clinical Characteristics of Post-surgical Ptosis Patients at Dr. Mohammad Hoesin General Hospital Palembang - Fadillah Amrina; Riani Erna; E. Iskandar (Sriwijaya Journal of Ophthalmology, 2022)
Introduction: Blepharoptosis is drooping of the upper eyelid in a primary position, causing the narrowing of the palpebral fissure. This condition can partially or completely cover the visual axis. Establishing the diagnosis of ptosis requires a comprehensive eye examination, including history taking, physical examination, and examination of the eyelids in ptosis patients. The majority of patients with ptosis require surgery, and clinical characteristics play an important role in classifying the type of ptosis and then formulating a detailed treatment plan strategy so that a better outcome is obtained. Methods: A descriptive retrospective study was conducted from medical records of post-surgical ptosis patients at Dr. Mohammad Hoesin Hospital Palembang from January 2016 to December 2021. The data taken included age, gender, the onset of occurrence, laterality, type of ptosis based on the onset, vertical palpebral fissure (FPV), horizontal palpebral fissure (FPH), margin-reflex distance (MRD), margin limbal distance (MLD), lid lag, bell's phenomenon levator muscle function, type of ptosis surgery and postoperative condition. This study aims to determine the clinical characteristics of patients with ptosis at Dr. Mohammad Hoesin Hospital Palembang. Results: Of the 57 ptosis patients in this study, the majority of patients were male, as many as 32 patients (56.1%) with the age category >40 years, as many as 24 patients (42.1%) with unilateral lateral ptosis as many as 50 patients (87.7%) with the more frequent comparison was the left eye in 29 patients (58%). Acquired ptosis was the most common cause in this study in as many as 46 patients (80.7%), and the most common mechanism of acquired ptosis was neurogenic (33.3%). The majority of patients had no previous surgical history of 41 patients (71.9%), moderate levator function of as many as 42 (73.7%), and frontal suspension surgery technique with synthetic materials as many as 17 (34%) patients. the mean FPV was 5.08±2.627 with a median of 5.00 (0-11), FPH 25.94±1.726 with a median of 26.00 (20-29), MRD 0.246±1.78 with a median of 0.00 (-4 -5), MLD 4.789±2.801 with a median of 5.00 (-4-11) and LA 7.16±4.083 with a median of 7.00 (0-14). Ptosis patients had negative lid lag in 47 patients (82.5%) and positive bell's phenomenon in 49 patients (86%). The postoperative condition of ptosis patients was satisfactory where there was no recurrence and reoperation of ptosis, postoperative complications as many as 1 (1.8%) patients experienced overcorrection, 6 (10.5%) patients experienced lagophthalmos, and 2 (3.5%) patients had an outcome. asymmetric. Conclusion: Clinical characteristics of ptosis patients can determine the diagnosis and treatment that will be given to the patient.